JUDGMENTS ISSUED IN THE AMPARO PROCESS AND THE THEORY OF LEGAL ARGUMENTATION IN NEOCONSTITUTIONALISM - Diana Milagros Dueñas Roque (2019)
In the current context of Law there is an overwhelming reality called the new Constitutionalism, a complex phenomenon that radiates to all legal systems that are part of the Anglo-Saxon, Romanic, Germanic, Islamic, etc. legal systems. The aforementioned legal reality obliges the public bodies to give valid reasons so that they can decide intersubjective conflicts, legal uncertainties, protection of constitutional rights, criminal offenses and others that require solution, therefore, there is a high demand for legal argumentation by of the justiciables. Legal argumentation is important, as it constitutes a further requirement for the aforementioned phenomenon to be witnessed, because it takes care of the construction of the syllogism, gives validity to the fundamentals used and finally persuades a specific audience under certain previous rules, that is, it passes from the individual to the social level, for the legitimacy of legal argumentation. The present investigation will be given in the Mixed Courts of the Superior Court of Justice of Puno - Puno headquarters, focusing on the sentences issued in the amparo proceedings, whose objectives are directed to the verification of whether the sentences are adequately argued according to the standard theory of legal argumentation within neo-constitutionalism. The methods that will be used are argumentative, deductive, analytical and synthetic.